CLINICAL AND EPIDEMIOLOGICAL CHARACTERISTICS OF ODONTOGENIC PURULENT-INFLAMMATORY DISEASES IN CHILDREN - Tasheva , G.; Inoyatov , A. (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
Odontogenic purulent-inflammatory diseases in children remain highly relevant due to their prevalence and risk of complications. This study analyzed 239 patients aged 3–17 years, considering age, gender, and premorbid background. The highest incidence was observed in adolescents (12–17 years), with a predominance of males. Premorbid conditions, particularly chronic tonsillitis, anemia, and ethmoiditis, were common and often combined. Submandibular and infraorbital phlegmons were the most frequent clinical forms. The findings emphasize the importance of early diagnosis and individualized treatment approaches in pediatric patients.